2012
DOI: 10.1007/s10047-012-0631-y
|View full text |Cite
|
Sign up to set email alerts
|

Aortic valve prosthesis selection in dialysis patients based on the patient’s condition

Abstract: Previous studies have examined outcomes in dialysis patients undergoing cardiac surgery. However, only a few studies have solely focused on outcomes after aortic valve replacement (AVR). This study aimed to clarify independent predictors of the long-term survival of dialysis patients with AVR and to determine whether a mechanical valve or bioprosthesis is suitable based on the patient's condition. A total of 38 consecutive dialysis patients who underwent AVR at our institute were reviewed (mean age 69.1 ± 9.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 22 publications
1
28
1
Order By: Relevance
“…After excluding duplicates, from 452 initial search results, 201 relevant abstracts were identified for secondary review. Finally, 15 retrospective studies fulfilled our inclusion criteria (Figure ). Two studies were excluded as they only selected patients with infective endocarditis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After excluding duplicates, from 452 initial search results, 201 relevant abstracts were identified for secondary review. Finally, 15 retrospective studies fulfilled our inclusion criteria (Figure ). Two studies were excluded as they only selected patients with infective endocarditis.…”
Section: Resultsmentioning
confidence: 99%
“…In 5523 and 1600 patients undergoing mechanical valve and biological valve replacement, respectively, 4115 aortic and 2112 mitral valves were replaced; there was variability in the specific valve type among the studies included. Three studies reported results of isolated aortic valve replacement. The duration of preoperative dialysis was reported in seven studies .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After exclusion of duplicate or irrelevant references, 40 potentially relevant articles were retrieved. After application of inclusion and exclusion criteria, 16 relevant articles were included in the present systematic review and meta-analysis (7,(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). A total of 8,483 patients with ESRD were included for analysis, including 6,187 receiving bioprosthesis and 2,296 receiving mechanical valves.…”
Section: Literature Searchmentioning
confidence: 99%